Hepatic Steatosis in Pulsed Field Ablation for Atrial Fibrillation: Prevalence, Liver Marker Concordance and Acute Procedural Characteristics - Maria Boszko; Bartosz Krzowski; Michał Gawlik; Alicja Skrobucha; Julia Szydlik; Mateusz Wawrzeńczyk; Karolina Mitrzak; Kacper Rutkowski; Karolina Ignaczak; Monika Gawałko; Cezary Maciejewski; Jakub Rokicki; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Hepatic steatosis and metabolic dysfunction-associated steatotic liver disease (MASLD) are cardiometabolic phenotypes relevant to atrial fibrillation (AF), but their prevalence and acute procedural relevance in pulsed field ablation (PFA) are poorly defined. We estimated the prevalence of hepato-renal index (HRI)-detected hepatic steatosis, assessed liver marker concordance, and explored acute procedural characteristics. Methods: In this single-centre prospective study, 99 consecutive eligible patients undergoing first-time PFA for AF underwent B-mode hepatic ultrasound. Hepatic steatosis was defined a priori as HRI ≥ 1.28, measured offline by an investigator blinded to clinical and procedural data. HRI-based MASLD-compatible phenotype, Hepatic Steatosis Index (HSI), BARD score, and Fibrosis-4 index were analysed as secondary liver markers. Results: HRI-detected hepatic steatosis was present in 62/99 patients (62.6%, 95% CI 52.8–71.5), and HRI-based MASLD-compatible phenotype in 55/99 (55.6%, 95% CI 45.7–65.0). Agreement between HRI and HSI was poor (Cohen’s κ = 0.01; prevalence-adjusted bias-adjusted κ +0.06; positive agreement 62%). Acute pulmonary vein isolation was achieved in all patients. First-pass isolation was high in both groups (91.9% vs. 81.1%; p = 0.124). Most procedural metrics were similar. Fluoroscopy dose was modestly higher in patients with steatosis (median 226 vs. 207 mGy; p = 0.035), but this exploratory signal was inconsistent across sensitivity analyses. In-hospital complications were infrequent (4/99, 4.0%). Conclusions: In first-time PFA patients with feasible HRI assessment, hepatic steatosis was common, liver marker classifications showed limited patient-level agreement, and acute procedural conduct showed no consistent steatosis-specific signal. Long-term rhythm durability requires dedicated follow-up.